2015
DOI: 10.1155/2015/953138
|View full text |Cite
|
Sign up to set email alerts
|

Weight Maintenance with Litramine (IQP-G-002AS): A 24-Week Double-Blind, Randomized, Placebo-Controlled Study

Abstract: Background. Litramine (IQP-G-002AS) was shown to be effective and safe for weight loss in overweight and obese subjects. However, long-term effectiveness on maintenance of body weight loss has yet to be ascertained. Objective. To assess effect of Litramine on maintenance of body weight loss. Methods. A double-blind, randomised, placebo-controlled trial on overweight and obese patients was conducted over two sites in Germany for 24 weeks. Subjects with documented previous weight loss of 3% over the last 3–6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…There were no differences in LBM, though both groups did lose LBM suggesting the fiber may have contributed to increased weight loss in the treatment group but did not effectively offset LBM losses in this study; from the total weight lost, the fiber group lost approximately 50% of LBM while the placebo group lost approximately 36% of LBM showing that the fiber did not offset LBM loss [39]. In a similar study conducted over six months, subjects maintained weight loss, but also lost LBM when compared to controls [33].…”
Section: Dietary Supplements and Body Compositionmentioning
confidence: 94%
See 1 more Smart Citation
“…There were no differences in LBM, though both groups did lose LBM suggesting the fiber may have contributed to increased weight loss in the treatment group but did not effectively offset LBM losses in this study; from the total weight lost, the fiber group lost approximately 50% of LBM while the placebo group lost approximately 36% of LBM showing that the fiber did not offset LBM loss [39]. In a similar study conducted over six months, subjects maintained weight loss, but also lost LBM when compared to controls [33].…”
Section: Dietary Supplements and Body Compositionmentioning
confidence: 94%
“…While CrP and other dietary supplements all lead to weight loss, a larger percent of the weight lost during these studies comes from a loss in LBM. CrP appears to offer an effective means of improving body composition, as individuals are able to lose their fat, while retaining their muscle [14,31,32,33,34].…”
Section: Figurementioning
confidence: 99%
“…Another double-blind, randomized, placebo-controlled study in overweight and obese subjects lasting 24 weeks demonstrated that after 24 weeks the number of responders was higher in Litramine ®treated subjects than in placebo individuals. At the end of the study the difference in weight between the groups was 2.2 kg; 92% in the Litramine ® group vs. 25% in controls managed to maintain the weight loss (Grube et al, 2015).…”
Section: Dietary Supplementsmentioning
confidence: 93%
“…The authors did not observe adverse effects after the ingestion of IQP G-002AS. Following the aforementioned study, the same authors in 2015 [31] conducted another double-blind, randomised study spanning twenty-four weeks. This design involved a cohort of subjects, both male and female volunteers with obesity aged between 18 and 60 years, with a BMI ranging from 25 to 35 kg/m 2 .…”
Section: Linarès Et Al (2007)mentioning
confidence: 99%